A pilot study on the effects of direct contact of two different surgical burs on the cadaveric lingual nerve - Al-Amery, Samah Mohammed; Ngeow, Wei Cheong; Nambiar, Phrabhakaran; Naidu, Murali (Elsevier, 2018)
The lingual guttering technique for third molar surgery carries the risk of injury to the lingual nerve if the surgical bur comes into direct contact with it. This study investigated the extent of nerve injury caused by two different burs, a tungsten carbide bur and the Dentium implant bur; the latter is designed to be soft tissue friendly. This study also examined whether ultrasound and magnetic resonance imaging are able to detect any injury inflicted. This cadaveric research involved subjecting 12 lingual nerves to the drilling effect of two different burs at two different speeds. The amount of damage caused was measured using different imaging modalities to assess their ability to detect the injury inflicted. At high speed, the Dentium bur caused a deeper and wider laceration than the carbide bur. At low speed, the laceration depths and widths caused by the two burs did not differ significantly. Ultrasound scanning was able to detect the nerve laceration at damaged sites observed using optical coherence tomography. Thus, a carbide bur (at low speed) would be preferable for lingual bone guttering, as it causes less laceration to the lingual nerve. In the event of a suspected injury, ultrasound scanning would provide an objective evaluation of the amount of nerve damage in vivo.